Pelaksaan Praktik Pagang Gadai Tanah Ulayat di Nagari Parik Panjang Kabupaten Agam Sumatera Barat - Ibnu Syechkant (Pemuliaan Keadilan, 2025)
There are several developments in the practice of pawn gates, on the condition that pawn gates can also be done for the educational needs of nephews or business capital. Developments in the use of transaction tools can now use money. Pagang gadai is known to have no redemption period, and the Wali Nagari Parik Panjang does not want to sign the pawn letter because it is against positive law in Indonesia. There is no legal protection for the implementation of the practice of pawning in the Minangkabau customary law community. This is because land pawning is carried out without registration. The settlement of the problem of pawn disputes in Nagari Parik Panjang, Matur District, Agam Regency using the principle of bajanjang naiak, batanggo turun means that it is resolved from the lowest level, namely deliberation and consensus, then the Nagari Customary Density, to the highest level, namely the court level.